2019
DOI: 10.1021/acs.joc.9b00318
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Induced Regioselective Cross-Dehydrogenative Coupling of 2H-Indazoles with Ethers

Abstract: A visible-light-promoted regioselective C­(sp2)–H/C­(sp3)–H cross-dehydrogenative coupling between 2H-indazoles and ethers has been achieved using a catalytic amount of rose bengal as an organophotoredox-catalyst and tert-butyl hydroperoxide (TBHP) as an oxidant at ambient temperature under aerobic conditions. A variety of C-3 oxyalkylated 2H-indazoles have been synthesized in moderate to good yields. Mechanistic studies suggest a radical pathway of the present reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 78 publications
(30 citation statements)
references
References 50 publications
1
27
0
2
Order By: Relevance
“…Our group was also actively involved for functionalization of 2 H -indazoles. 15 Very recently, our group reported phosphorylation of 2 H -indazole with diphenylphosphine oxide via visible light photoredox catalysis. 15b But in our previous conditions 15b phosphonate ester did not react with 2 H -indazole.…”
Section: Introductionmentioning
confidence: 99%
“…Our group was also actively involved for functionalization of 2 H -indazoles. 15 Very recently, our group reported phosphorylation of 2 H -indazole with diphenylphosphine oxide via visible light photoredox catalysis. 15b But in our previous conditions 15b phosphonate ester did not react with 2 H -indazole.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, functionalizations using environment‐friendly catalysts such as organophotocatalysts are the most demanding among synthetic organic chemists as these methods can reduce the requirement of high temperature and toxicity [74–79] . In 2014, Yadav et al [56] .…”
Section: Different Oxosulfonylation Methodsmentioning
confidence: 99%
“…Recently, functionalizations using environmentfriendly catalysts such as organophotocatalysts are the most demanding among synthetic organic chemists as these methods can reduce the requirement of high temperature and toxicity. [74][75][76][77][78][79] In 2014, Yadav et al [56] revealed a metal-free method for one-pot synthesis of a series of β-keto sulfoxides. Alkenes 14a reacted with aryl thiophenols 14b in presence of eosin Y as photocatalyst in acetonitrile solvent under irradiation of green light to afford β-keto sulfoxides 14c in 65-90% yields.…”
Section: In Alkene Systemmentioning
confidence: 99%
“…of DABCO as an additive at room temperature under blue light irradiation for 24 h. The desired C-3 oxyalkylated 2H-indazole derivatives (82 b) were formed with good to excellent yields (Scheme 82). [68] Both cyclic and acyclic ethers responded to the reaction and gave corresponding C-3 oxyalkylated indazole products. This reaction was tolerant of different substitutions at the aryl part of 2H-indazole.…”
Section: Brominationmentioning
confidence: 99%
“…Our group has developed several functionalization methods for indazole derivatives. [63][64][65][66][67][68] indazole, herein, we first report a brief review on direct functionalizations including arylation, alkylation, acylation, alkenylation, alkynylation, trifluoromethylation, selenylation, nitration, cyanation, bromination, carbonylation and oxyalkylation of indazole derivatives. This article covers most of the related papers published in the last 20 years.…”
Section: Introductionmentioning
confidence: 99%